The relationships between intangible organizational elements and organizational performance - Carmeli, Abraham; Tishler, Ashler (Strategic Management Journal, 2004)
Abstract Despite the growing awareness of the importance of researching core strategic resources and activities, the work that has been done to date has largely taken the form of anecdotal reports and case study analysis. We have yet to see large‐sample studies demonstrating how organizational elements, independently, complementarily and interactively, may or may not enhance the organization's performance. Moreover, little attention has been given to researching this topic in public sector organizations. The present study aims to bridge this gap by examining the impact of a set of independent intangible organizational elements and the interactions among them on a set of objective organizational performance measures in a sample of local government authorities in Israel. The results of a multivariate analysis indicate that organizational performance (measured by self‐income ratio, collecting efficiency ratio, employment rate, and municipal development) can be well explained by six intangible organizational elements (managerial capabilities, human capital, internal auditing, labor relations, organizational culture, and perceived organizational reputation) and the interactions among them, which need to be taken into account in any cost effective development. Copyright © 2004 John Wiley & Sons, Ltd.